Improving faba bean production and productivity through the integrated management of Orobanche Crenatae at Kutaber, Amhara Region, Ethiopia - Akalu Gebru; Mekonnen Mesganaw (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Orobanche crenata (parasitic weed) is highly limiting factor for faba bean productions and the most serious agricultural economic importance pests in south wollo, eastern Ethiopia. Orobanche infested areas located in Eastern Amhara, Kutaber, Dessie zuria, Tenta and Mekedella distinct which are 40- 120 km far from the capital city of South Wollo zone Dessie. Kutaber and Dessie zuria districts were more infested for orobanche and makes out of production for the last 30 years.  To regenerate faba bean production in the given districts Sirinka Agricultural Research Center in collaboration with ICARDA project have done different research activity on orobanche parasitic weed controlling methods using different synthetic chemical spray, chemical integrating with other cultural, and chemical methods, through different plant growth  stage. Ashenge faba bean variety (orobanche tolerant) with two times of 0.3Lha-1 glyphosate chemical in 250 to 300Lha-1 water sprayed at faba bean flower starting & one week after first sprayed, and continuous hand weeding of orobanche weed before flowering. With these integrated management the Ashengie variety gave 22-26qtha-1 in the orobanche infested areas. .There was a  wide training addressed for 112 male and 23 female. Total 135 participants attend at Kutaber district. The training addressed how to produce pure and quality seed production using 0.3L of Glyphosate chemical with Ashengie Variety to replace faba bean production and supplying for income generation of the farmer. Ashengie variety seed exchanged were 18.5 quintal among farmer using 4 male, 2 female, totally 6 in 2017 and the exchange in kind with any crop were 15.5 quintal seed for quality seed around Orobanche infested areas. From the above result total sale price reach 32000.00 Birr per 1 ton and  farmer were more benefited in seed sales and used as seed source for Orobanche contaminated areas.